2020
DOI: 10.1590/s1678-3921.pab2020.v55.01587
|View full text |Cite
|
Sign up to set email alerts
|

Survival and initial growth in the field of eucalyptus seedlings produced in different substrates

Abstract: The objective of this work was to evaluate the survival and initial growth, in the field, of eucalyptus seedlings produced in different substrates. Eucalyptus benthamii seedlings produced in 36 substrates were evaluated in the field. The substrates consisted of mixtures, at different volumetric proportions, of: carbonized rice husk, charcoal with granulometry between 1.0-3.0 mm, charcoal with granulometry between 3.0-5.0 mm, coconut fiber, semi-decomposed pine bark, fine vermiculite, sewage sludge, and peat mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
(32 reference statements)
1
5
0
2
Order By: Relevance
“…Concerning different CRF doses, the values frequently higher for height and stem diameter in response to an increase in doses reinforce results that point to better seedling development under greater nutrients availability [6,31]. According to some authors, seedling quality has a high correlation with height and stem diameter, generating higher rates of survival and growth in the field [32,34] and, consequently, higher financial returns than those obtained through low-quality seedlings [35]. Thus, several studies have indicated the use of fertilizer to improve growth of yerba mate seedlings, mainly through N, P, and K availability [6,17,31].…”
Section: Discussionsupporting
confidence: 58%
“…Concerning different CRF doses, the values frequently higher for height and stem diameter in response to an increase in doses reinforce results that point to better seedling development under greater nutrients availability [6,31]. According to some authors, seedling quality has a high correlation with height and stem diameter, generating higher rates of survival and growth in the field [32,34] and, consequently, higher financial returns than those obtained through low-quality seedlings [35]. Thus, several studies have indicated the use of fertilizer to improve growth of yerba mate seedlings, mainly through N, P, and K availability [6,17,31].…”
Section: Discussionsupporting
confidence: 58%
“…Stem diameter was also influenced by substrates, although all the substrates allowed the growth of seedlings with an adequate diameter for outplanting, similar to those obtained by Navroski et al (2016). Stem diameter is considered the best morphological attribute to forecast field growth, especially because it correlates with seedling weight and root system size (Stuepp et al 2020). Ivetić et al (2016) highlight that this morphological characteristic well correlates with initial growth in the field, although it is unable to predict seedlings' survival.…”
Section: Seedling Growthmentioning
confidence: 56%
“…Studies conducted in nurseries are based on morphological or physiological variables to determine seedling quality, however, it is important to relate seedlings characteristics to its survival after planting in the field (Grossnickle & MacDonald 2018, Stuepp et al 2020. The variables most used to determine forest seedlings' quality are height and stem diameter because the measurement is simple, fast, and non-destructive (Ivetić et al 2016).…”
Section: Seedling Growthmentioning
confidence: 99%
“…This period was frequently used by most plantation forests company in Indonesia to conduct the first evaluation of planting trials (Wirabuana et al 2019). The period was a critical moment to assess the adaptability of species to environmental conditions outside their natural habitat (Stuepp et al 2020). The process of data collection was conducted from March to April 2021, consisting of several activities, i.e., stand measurement, destructive sampling, and laboratory analysis.…”
Section: Data Collectionmentioning
confidence: 99%
“…A preliminary evaluation was undertaken to monitor the growth, aboveground biomass, crown development, and leaf characteristics of those three species at six months after planting. It is a critical period to assess the suitability of species to survive in the site condition (Van Bich et al 2019;Stuepp et al 2020;Wirabuana et al 2020a) since every eucalyptus species has a habitat preference to support its growth and development. If site condition is not suitable, the species will demonstrate a high mortality rate and low growth performance (Thompson 2013;Maimunah et al 2018;Aguilos et al 2020).…”
Section: Introductionmentioning
confidence: 99%